Tracing the Trialectic: The Process and Influence of Three Laws in the Establishment of Religious Courts in Indonesia - Moh. Muafiqul Khalid MD; Aldi Hidayat; Muhammad Alan Juhri; Elvina Lintang Solehah (Justicia Islamica, 2024)
This article discusses the legal trialectic in establishing the Religious Courts in Indonesia. Since its establishment in 1882, the Religious Courts have not fully represented Islamic law as its primary source. To trace this trialectic, the author uses Ebrahim Moosa's theoretical framework of "transculturation, counterpoints, social imaginary, networks, and legal orientalism." For this purpose, the author proposes two problem formulations. First, what is the process of trialectic attraction between Islamic law, positive law, and customary law in the establishment of the Religious Courts? Second, what is the extent of the influence of positive and customary law in limiting the role of Islamic law? The author offers two novelties, namely methodological novelty in Indonesian Islamic studies, by adopting Ebrahim Moosa's theory. Finally, the conclusive novelty is that the Religious Court is not derived from Islam but from the trialectic of three laws. The practical contribution of this study is to re-question the roles of religious courts in formalizing and implementing Islamic law in Indonesia, with the hope that religious courts will become a dialectical space where Islamic law continues to develop so that it can make a practical contribution to contemporary Indonesian society.